Penguatan Kelembagaan Pimpinan Ranting Aisyiyah melalui Inisiasi Prosedur Litigasi dan Non Litigasi Penanganan Kasus Kekerasan Terhadap Perempuan - Ria Angin; Fauziyah Fauziyah (Indonesian Journal Publisher, 2022)
This volunteer effort intends to help the Aisyiyah Branch Leader of the Jember Regency deal with instances of abuse against women. To address cases of abuse against women, both non-litigation and litigation strategies are used. The overall number of participants in all the action was 50 (fifty). Three (3) steps make up the execution of this community service: preparation, performance, and evaluation. There were two activities before the event: (1) Through the distribution of questionnaires, the community service activities confirmed to the Aisyiyah Branch Manager the types of violent cases that had happened and the breadth of the handling efforts that had been made in the working area of the Aisyiyah Sumbersari Branch Manager, Jember Regency. (2) The service project delivery includes data processing from the distributed surveys. (3) The activity's organizer must create the materials necessary by the Aisyiyah Branch Managers in the office of the Aisyiyah Sumbersari Branch Manager, Jember Regency, based on the data acquired regarding the various types of violence. The primary topic of the literature is litigation, or the processes used to adjudicate cases of victimized violence in court system. While the purpose of non-litigation is to help by using alternate techniques without going through legitimate methods. According to the evaluation of the activities, the Aisyiyah Branch Leaders in the Jember Regency-managed Aisyiyah Sumbersari Branch are better able to handle situations of violence against women.